Does lung microbiome play a causal or casual role in asthma?. Issue 10 (26th June 2018) - Di Cicco, Maria; Pistello, Mauro; Jacinto, Tiago; Ragazzo, Vincenzo; Piras, Martina; Freer, Giulia; Pifferi, Massimo; Peroni, Diego
Abstract: Asthma is the most common chronic disease in childhood. The pathogenesis of asthma is multifactorial and is thought to include environmental factors interacting with genetics during pregnancy and in the first years of life. In the last decades, a possible role of gut microbiota in allergic disease pathogenesis has been demonstrated. Next generation sequencing techniques have allowed the identification of a distinct microbiome in the healthy lungs. The lung microbiome is characterized by the prevalence of bacteria belonging to the phylum Bacteroidetes (mostly Prevotella and Veilonella spp) in healthy subjects and to the phylum Proteobacteria in asthmatics (mostly Haemophilus, Moraxella, and Neisseria spp). In asthma, as well as in other diseases, the lung microbiome composition changes due to a disruption of the delicate balance between immigration and elimination of bacteria. The lung microbiome can interact with the immune system, thus influencing inflammation. Early infections with viruses, such as respiratory syncytial virus, may alter lung microbiome composition favoring the emergence of Proteobacteria, a phylum which is also linked to severity of asthma and bronchial hyperreactivity. Lastly, antibiotics may alter the gut and lung microbiota and potentially disturb the relationship between microbiota and host. Therefore, antibiotics should be prescribed with increasing awareness of their potential harmful effect on the microbiota in young children with and without asthma. The potential effects of probiotics and prebiotics on lung microbiome are unknown.